Serum Uric Acid, A Predictor of Fetal Outcome at Birth in Pre-eclampsia - Nazneen Akhtar, Lubna Khan, Naila Javed, Sobia Jamal, Hafsa Riaz, Iqra Mushtaq (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the association of serum uric acid levels with adverse fetal outcomes at birth among women with pre-eclampsia. Study design: Prospective cohort study Place and duration of study: Department of Gynaecology and Obstetrics, KRL Hospital Islamabad from April 2023 to September 2023. Methodology: A total of 50 women with singleton pregnancy diagnosed with pre-eclampsia and having serum uric acid levels ≥5.5 mg/dL were included in Group-A, while another 50 women with same clinical characteristics and having serum uric acid levels ˂5.5 mg/dL were included in Group-B. Fetal outcomes at birth were assessed including low birth weight, preterm birth, APGAR score at 1 and 5 minutes, neonatal intensive care unit admission and stillbirth. Association between elevated serum uric acid levels and adverse fetal outcomes was evaluated by performing relative risk analysis with 95% confidence intervals, taking a p-value <0.05 as statistically significant. Results: The mean age of women was 33.24±5.61 years in overall study population. Comparison of fetal outcomes revealed a significantly higher incidence of adverse fetal outcomes in Group A compared to Group B including the incidence of low birth weight (RR 1.87, 95% CI 1.14–3.05, p=0.01), preterm birth (RR 2.33, 95% CI 1.19–4.58, p=0.01), low APGAR scores at 1 min. (RR 2.29, 95% CI 1.03–5.07, p=0.03), and neonatal intensive care unit admissions (RR 4.50, 95% CI 1.02–19.79, p=0.03). Conclusion: Elevated serum uric acid levels are strongly associated with adverse fetal outcomes in pre-eclamptic pregnancies. Keywords: Newborn, Pre-eclampsia, Pregnancy outcome, Uric acid.